The house of hidden meanings : a memoir - RuPaul, 1960- (Dey St., an imprint of William Morrow, 2024)
From an international drag superstar and pop culture icon comes his most revealing and personal work to date-a deeply intimate memoir of growing up black, poor and queer in a broken home and discovering the power of performance, found family and self-acceptance.